Jaw Osteonecrosis Preceded by Dengue Fever - Possible Pathogenetic Mechanism - Patil, Purva Prakash (J Orthop Case Rep, 2018)
INTRODUCTION: Osteonecrosis of jaw (ONJ) is a debilitating condition which can lead to compromised dentition. Various causes for ONJ are suggested in the literature such as drugs, trauma, radiation, chemicals, bacterial, and fungal infections. Knowing etiology for particular case of ONJ is important to prevent further progression of this debilitating condition. It is the first case of ONJ reported with dengue virus as a possible etiology. CASE REPORT: This article presents a case of 46-year-old male patient with extensive osteonecrosis of maxilla preceded by dengue fever. In the present case, all known causes for osteonecrosis were ruled out. The present article discusses dengue infection as a possible etiologic agent for ONJ. CONCLUSION: In the present case, probable cause for ONJ can be established as a dengue virus necessitating the need for proper preventive methods to avoid further complication of osteonecrosis.